P13 Introduction of calorie posting in a university teaching hospital staff canteen: staff perceptions and resulting purchasing patterns differ according to gender. (3rd September 2019) - Flood, C; Cunniffe, E; Doherty, K; Lyons, A; Stynes, S; Pilkington, A; Barnes, L; Peare, T; Kelleher, C; Fitzpatrick, P
Abstract : Background: Restaurants in Ireland will be required by law to display calorie counts on menus by end of 2019 as part of the strategy to combat obesity. Such initiatives are not always systematically evaluated. As part of the current National Healthy Ireland policy initiative, since September 2018 the introduction of calorie posting in hospitals is now Health Service Executive (HSE) policy also. The purpose of calorie posting is to promote awareness and increase consumption of healthier food and drink choices amongst HSE staff and the public using and visiting HSE healthcare facilities. Methods: The Health Promotion, Dietetics and Catering teams worked together to introduce both calorie posting and a traffic light system (TLS) for all foodstuffs and meals available in the main staff canteen in a large University teaching hospital. One month after the calorie posting launch day, a survey of staff members was undertaken over a working week-period (at 3 time points daily coinciding with main meals) to assess their perceptions. A short pre-designed Sphynx-software questionnaire was either interview or self-administered and left afterwards in drop-box. Analysis was conducted using SPSS. Results: In all 343 questionnaires were returned (65.3% female; 18–44 years 65.3%, 45+ 32.1%, age unknown 2.6%). More staff found calorie posting helpful compared to TLS (66.5% vs 43.7%; p=0.001). More females than men found both calorie posting (72.3% vs 53.3%; p=0.001) and TLS (49.1% vs 31.8%; p=0.001) helpful. 46% made themselves aware of calorie count always/mostly and 26.2% sometimes. More identified calorie posting as influencing food choice at least sometimes than TLS (60.3% vs 36%; p=0.0001) Females were more likely to make a food choice change based on TLS (39.7 vs 20.6%; p=0.01). Age and frequency of canteen use were not associated with either. Conclusion: The results suggest significant gender differences in that calorie posting is more used than the TLS and females are more likely to use both. Although self-selection may affect findings, nonetheless there were important moves in both genders and all ages to make healthier choices. Impact of price was not assessed. Health promotion strategies should account for gender preferences.